FRI0130 Certolizumab pegol exposure during pregnancy in women with rheumatoid arthritis: evaluation of the long-term newborn outcomes. (12th June 2018) - Meroni, M.; De Santis, M.; Caprioli, M.; Ceribelli, A.; Isailovic, N.; Rossi, P.; Cutolo, M.; Selmi, C.
Abstract : Background: Increased TNF alpha (TNFα) levels have been associated to pregnancy complications such as intra-uterine growth retardation and fetal loss. Even if pregnancy has classically been considered as having a positive impact on RA, disease flares potentially leading to poor obstetrical outcomes are not uncommon, raising the challenge of RA management in the early stages of pregnancy. Among TNFα inhibitors indicated for rheumatoid arthritis (RA), the use of certolizumab pegol (CTZ) has been reported as safe during pregnancy. As such, CTZ is allowed during pregnancy as provided by the factory-issued product's sheet. Objectives: To assess the CTZ use safety during RA pregnancies, including maternal-fetal outcomes. Methods: We retrospectively evaluated twelve women with RA, fulfilling the 2010 ACR/EULAR criteria, who had been exposed to CTZ throughout pregnancy. All women had signed an informed consent prior to treatment initiation. Results: All cases were free from any potentially teratogenic drug, stopped at least 6 months before conceiving. Due to the underlying disease activity, and thanks to the approval for CTZ to be continued throughout the whole pregnancy, we carried on the treatment. Mean maternal age at conception was 31.6±40 months; mean disease duration dated of 51±26 months. All patients were on low-dose daily oral prednisone ranging from 2.5 to 5 mg; four subjects were on sulfasalazine 500 mg TID and four others on hydroxychloroquine 200 mg TID. We observed 12 singleton pregnancies; 8/12 mothers were primiparous. Mean gestational duration was 37±3 weeks and mean birth weight 3.037±0.58 grams. No stillbirths or fetal deaths were recorded. Five patients experienced elective caesarean section, while the others had vaginal delivery (four labour were induced by intravenous oxytocin; no dystocic births were reported). Mean APGAR scores after 1, 5 and 10 min from delivery were, respectively, 8±2; 8±1 and 9±1. No obstetric, perinatal or neonatal complications were observed. Eight/12 newborns were breastfed. After a 12 months observational gap, all babies were healthy and the development index above the 75th percentile. All children underwent the Italian scheduled vaccine program, without complications. Their antibody vaccine response is nowadays being investigated by our Research team. Conclusions: The data from our case series confirm the safety of CTZ administration during pregnancy in women with RA, regarding both the mothers and the offspring. No infection rate increase, neither major maternal-fetal issue were reported. The higher caesarean section rate in our patients, in comparison to the average of northern Italy (20%), could have a iatrogenic explanation, as suggested by the fact that all had been scheduled ahead of time. Similarly, the relative low rate of breastfeeding could be justified by the lack of information given to mothers. Further large data collection and perspective, controlled studies are needed to confirm this statement. References: [1] Mariette X, et al. Ann Rheum Dis. 2018;77(2):228–233. [2] Förger F, et al. Joint Bone Spine. 2016;83(3):341–3. [3] Clowse ME, et al. J Rheumatol. 2015;42(12):2270–8. Disclosure of Interest: None declared